The Metabolomic Characterization of Different Types of Coronary Atherosclerotic Heart Disease in Male - Yuxuan Fan; Xianglan Quan; Shengquan Liu; Le Yue; Jizong Jiang; Zhiqing Fan (Cardiology Research and Practice)
Background. In clinical practice, many patients with coronary atherosclerotic heart disease (CAD) have atypical clinical symptoms. It is difficult to accurately identify stable CAD or unstable CAD early through clinical symptoms and coronary angiography. This study aimed to screen the potential metabolite biomarkers in male patients with stable CAD and unstable CAD. Methods. In this work, the metabolomic characterization of the male patients with healthy control (n = 42), stable coronary artery disease (n = 60), non-ST-elevation acute coronary syndrome (n = 45), including prepercutaneous corona intervention (n = 14), and postpercutaneous coronary intervention (n = 31) were performed by using ultra-performance liquid chromatography-mass spectrometry (UPLC-MS). The serum samples of patients were analyzed by multivariate statistics. Results. Results showed that 17 altered metabolites were identified to have a clear distinction between the stable CAD group and the healthy subjects. Compared with the stable coronary artery disease group, 15 specific metabolite markers were found in the acute coronary syndrome group. The percutaneous coronary intervention also affected the metabolic behavior of patients with CAD. Conclusions. In summary, CAD is closely related to energy metabolism, lipid metabolism, and amino acid metabolism disorders. The different metabolic pattern characteristics of healthy, stable coronary artery disease and acute coronary syndrome are constructed, which brings a novel theoretical basis for the early diagnosis of patients with stable and unstable CAD.